Ceiling Board Development Using Bamboo and Polypropylene as An Alternative to The Ceiling - Huttiff, Fitrie; Harun, Hasnida (Progress in Engineering Application and Technology, 2022)
To solve the problems of bamboo waste. To create and test an eco-ceiling board made from bamboo waste and polypropylene. This research focuses on the manufacturing of bamboo ceilings with high durability and strength requirements, as well as good sound absorption. For the sample 1, Polypropylene 90% was 144 grams, bamboo powder 6% was 9.6 grams and resin carbon 4% was 6.4 grams. Then for sample 2, Polypropylene 80% was 128 grams, bamboo powder 12% was 19.2 grams and resin carbon 8% was 12.8 grams. Next for the sample 3, Polypropylene 70% was 112 grams, bamboo powder 18% was 28.8 grams and resin carbon 12% was 19.2 grams. Last, for the control sample, Polypropylene 70% was 112 grams and bamboo powder 30% was 48 grams. The tensile strength MPa of sample 3 is 58.2 MPa is higher values and 46.06 MPa is low values for sample 1. The Young’s Modulus GPa of sample 2 is 16.75 GPa is higher values and 14.48 GPA is low values for sample 1. The water absorption of sample 3 is 1.48% is higher value and lowest value was 1.12% for control sample. The thermal conductivity of sample 1 is higher and lowest values for thermal conductivity is sample 2. Besides that, thermal resistance of sample 2 is higher values thermal resistance and the lowest values for thermal resistance is sample 1. The Sound absorption coefficient continuous of sample 3 is higher values sound absorption and sample 1 is low values of sound absorption.